1972
DOI: 10.1073/pnas.69.6.1467
|View full text |Cite
|
Sign up to set email alerts
|

Conformationally Dependent Low-Frequency Motions of Proteins by Laser Raman Spectroscopy

Abstract: Low-frequency Raman bands (lower than 50 cm-') exist in certain proteins. They are dependent upon the conformation of the protein molecule, but are relatively independent of the form of the sample, i.e., whether it is a film or a crystal.Low-frequency Raman spectra were obtained from samples of a-chymotrypsin that had been prepared in several ways. A peak at about 29 cm-' was found for all samples except the one that had been denatured with sodium dodecyl sulfate. Such low frequency motions must arise from vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(83 citation statements)
references
References 11 publications
6
75
0
Order By: Relevance
“…relative permittivity) of the medium [31]. Assuming the plasma membrane is such a medium, we can then attribute the physical origin of¯ to the resting membrane potential, and calculate¯ using equation (21), namelȳ = qE 0 R/( Ω). For many cells the values of the E 0 and d are well established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…relative permittivity) of the medium [31]. Assuming the plasma membrane is such a medium, we can then attribute the physical origin of¯ to the resting membrane potential, and calculate¯ using equation (21), namelȳ = qE 0 R/( Ω). For many cells the values of the E 0 and d are well established.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the first and second sums in the expression for H p represent, respectively, the kinetic and potential energies of the lattice. We take the value of Ω to be the natural angular frequency of slow phonons in an α-helix, Ω = 5.5 × 10 12 s −1 [21][22][23]. To derive the interaction Hamiltonian,Ĥ int , Davydov and Scott assumed that the energy of an on-site excitation depends on lattice deformations in its vicinity.…”
Section: The Model and Dynamical Equationsmentioning
confidence: 99%
“…For this reason, we have followed previous authors [3] and have made measurements on dry alpha-C. As Peticolas [4] has pointed out, when large molecules are in solution, the viscosity of the solvent will dampen the low frequency oscillations of the molecules and, if there are strong random fluctuating forces due to Brownian motion, these low frequency oscillations may acquire a stochastic character. However, if damping is not too severe, one might expect the resultant oscillations to have very nearly the same spatial displacements as their harmonic counterparts.…”
Section: Introductionmentioning
confidence: 97%
“…Subsequently, a number of neutron scattering and other experimental and computer simulation studies on various biological systems have revealed that many proteins exhibit this temperature-dependent dynamical transition around 180-220K (12,13,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Dynamics Protein Glass Transitionmentioning
confidence: 99%